Penerapan Model Group Investigation Terhadap Hasil Belajar Ilmu Pengetahuan Sosial Siswa Kelas IV SDN 10 Ganting Padang - Yulfia Nora; Yolanda Febrina (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
This research was motivated by the learning process carried out by the teacher who tended to use the lecture and question and answer method so that student learning outcomes were still low. This research aims to determine the effect of the application of the group investigation learning model on the social studies learning outcomes of the fourth-grade students of SDN 10 Ganting Padang. This type of research is experimental research. The sample in this study were students of class IV A and IV B with a total of 55 students. Data collection techniques in this study using tests. From the research results, it is known that the average social studies learning outcomes of the experimental class students were 82.57 and the control class was 76.74. The based on the results of the hypothesis analysis using the t-test, it is known that tcount> table, with a count of 1.87 and at-table value of 1.67 at a significant significance level of 0.05, meaning that H1 is accepted. From these results, it can be concluded that there is an effect of the application of the group investigation model on the IPS learning outcomes of the fourth-grade students of SDN 10 Ganting Padang.